Communication Beginnings An Introductory Listening and Speaking Text for English Language Learners - Abrahams, Della Jean (Open textbook library., 2017)
This textbook is designed for beginning-intermediate English language learners. It is composed of 7 chapters, each of which covers specific speaking and listening learning objectives and includes dialogues, interviews, discussions and conversation activities. Each chapter includes listening and speaking components such as dialogues, interviews, discussions and conversation activities. Each chapter also focuses on 10 target words from the New General Service List of English vocabulary. The textbook includes an audio component that consists of recorded conversations of native and non-native English speakers, as well as links to additional listening resources on the web.